2002
DOI: 10.1093/genetics/161.4.1713
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Gene Function in the Solanaceae as Revealed by Comparative Mapping of Domestication Traits in Eggplant

Abstract: Quantitative trait loci (QTL) for domestication-related traits were identified in an interspecific F2 population of eggplant (Solanum linnaeanum × S. melongena). Although 62 quantitative trait loci (QTL) were identified in two locations, most of the dramatic phenotypic differences in fruit weight, shape, color, and plant prickliness that distinguish cultivated eggplant from its wild relative could be attributed to six loci with major effects. Comparison of the genomic locations of the eggplant fruit weight, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(50 citation statements)
references
References 37 publications
(6 reference statements)
4
46
0
Order By: Relevance
“…Previously, a QTL for fruit width was also detected in chromosome 7 in an F2 intraspecific eggplant population [83]. In addition, other QTLs associated with fruit width were detected scattered over six chromosomes (1, 2, 3, 8, 10, and 11) in several eggplant populations, such as the ILs of S. incanum [86], an S. linnaeanum × S. melongena F2 population [81,87], and the 191 eggplant accessions panel [77].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previously, a QTL for fruit width was also detected in chromosome 7 in an F2 intraspecific eggplant population [83]. In addition, other QTLs associated with fruit width were detected scattered over six chromosomes (1, 2, 3, 8, 10, and 11) in several eggplant populations, such as the ILs of S. incanum [86], an S. linnaeanum × S. melongena F2 population [81,87], and the 191 eggplant accessions panel [77].…”
Section: Discussionmentioning
confidence: 95%
“…For the three traits related to the presence of prickles (P-StPrick, F-LeafPrick, and F-CalPrick) we detected three QTLs (ps6, pl6, and pc6, respectively) located at the same position on chromosome 6, indicating a common genetic basis for these three traits. Previously, QTLs related to prickliness were mapped in chromosome 6 [80] in an S. linnaeanum × S. melongena F2 population [76,81], in a BC1 population of the ILs of S. incanum × S. melongena [82], in an F2 intraspecific population [83], and in a panel of 191 accessions of breeding lines, old varieties, and landrace selections of eggplant [77], supporting that a major gene conserved in the eggplant group is present in this region [84,85]. For fruit traits, a QTL was detected for fruit width (F-Width) on chromosome 7 (fw7).…”
Section: Discussionmentioning
confidence: 99%
“…The wild ancestor species S. pimpinellifolium develops inflorescences with more than twice the number of flowers compared with domesticated types. The genetic architecture of flower number variation was dissected by classical linkage mapping, which revealed a polygenic nature of the trait ( Grandillo and Tanksley, 1996 ; Doganlar et al, 2002 ; Van Der Knaap and Tanksley, 2003 ). Although the causative gene variants still remain to be identified it has been suggested that the number of flowers per inflorescence is affected by the antiflorigen SP ( Grandillo and Tanksley, 1996 ).…”
Section: Optimizing Inflorescence Architecture By Tuning the Rate Of Meristem Maturationmentioning
confidence: 99%
“…None of the putative orthologs had clear functions related to domestication traits in eggplant. In addition, we identified the genomic coordinates of molecular markers under the QTL peaks from the Doganlar et al (2002) study and the prickliness indel marker from Miyatake et al (2020) ( Supplementary Table 2 ). In only one case was there overlap with a selective sweep; this was for the shoot anthocyanin QTL sa6.1 which overlapped with sweep 6_2 on chr 6.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work to identify the genomic regions underlying phenotypes in eggplants have largely taken a top-down approach, most often analyses of quantitative trait loci (QTL). These analyses have revealed loci linked to domestication traits using crosses between domestic and wild eggplant parents ( Doganlar et al 2002 ; Frary et al 2014 ; Portis et al 2014 ; Toppino et al 2016 ; Miyatake et al 2020 ), and loci controlling specific traits that vary between cultivars such as disease resistance ( Barchi et al 2018 ), and anthocyanin content ( Barchi et al 2012 ).…”
mentioning
confidence: 99%